1994
DOI: 10.1093/ajcn/60.5.782
|View full text |Cite
|
Sign up to set email alerts
|

Relation of maternal zinc nutriture to pregnancy outcome and infant development in an Egyptian village

Abstract: Zinc nutriture of women living in a periurban Egyptian village was examined over the last 6 mo of pregnancy and the first 6 mo of lactation as one of several potential determinants of pregnancy outcome and infant development. Estimated bioavailable zinc intake was approximately 2 mg/d from diets high in phytate and fiber. Among numerous variables analyzed by multiple regression, early pregnancy weight (3 mo) and plasma zinc concentrations in the second trimester formed the best predictor model of birth weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 44 publications
6
60
0
4
Order By: Relevance
“…However, the relationship between maternal zinc status and the child's cognitive development has not been fully investigated. In an observational study, low maternal zinc intake in Egyptian mothers was associated with lower levels of focused attention in newborns, measured with the Brazelton Neonatal Behavior Assessment Scale (Kirksey et al, 1994). Surprisingly, a placebo controlled randomized trial undertaken on poor Bangladeshi mothers found that 13 months old infants of zinc supplemented mothers scored less on the Bayley scales of infant development than infants born to mothers who received a placebo (Hamadani et al, 2002).…”
Section: Zincmentioning
confidence: 97%
“…However, the relationship between maternal zinc status and the child's cognitive development has not been fully investigated. In an observational study, low maternal zinc intake in Egyptian mothers was associated with lower levels of focused attention in newborns, measured with the Brazelton Neonatal Behavior Assessment Scale (Kirksey et al, 1994). Surprisingly, a placebo controlled randomized trial undertaken on poor Bangladeshi mothers found that 13 months old infants of zinc supplemented mothers scored less on the Bayley scales of infant development than infants born to mothers who received a placebo (Hamadani et al, 2002).…”
Section: Zincmentioning
confidence: 97%
“…Kirksey et al (77) observed positive associations between maternal serum zinc concentrations during pregnancy and the developmental status of Egyptian newborns assessed by using the Brazelton Neonatal Behavioral Assessment Scale (78). Subsequently, Kirksey et al (8) reported that positive associations were still observed between maternal zinc status during pregnancy and infant developmental status when assessed at 6 mo of age by using the Bayley Scales of Infant Development (79).…”
Section: Neurobehavioral Developmentmentioning
confidence: 99%
“…Importantly, the orientation and habituation components of both these tests were associated most strongly with maternal zinc status, and these are believed to relate directly to cognitive ability later in life (8). Orientation refers to the ability of the infant to respond appropriately to an environmental stimulus, whereas habituation refers to the ability of the infant to inhibit response to a repetitive or familiar environmental stimulus.…”
Section: Neurobehavioral Developmentmentioning
confidence: 99%
See 2 more Smart Citations